Impact of Climate Change on University Administration in Nigeria - Ohibime, Ernest Ohiosumua; Kingsley, EDINOH (International Journal on Integrated Education, 2023)
The objectives of this study is to find out the impact of climate change on university administration in Nigeria North-central political zone, Nigeria. The study adopted survey method. The population of the study was made up of academic staff and non-academic staff of public universities in the zone. Purposive sampling method was used to select the respondents. Questionnaire was used as data collecting instrument in the study. The questionnaire was titled (Impact of climate change on university administration in Nigeria Questionnaire). Reliability obtained was established at 0.86 and 0.88 respectively using the Kinder Richardson Formula. Data were analyzed using descriptive statistics of mean, and standard deviation. The result collected sowed that climate change (heavy rains and floods) have led to suspension of university administration, prevented universities’ administrators from going to offices and increases the administrative cost of the universities in the of repairs and reconstruction of damages facilities. The result also revealed that climate change (heavy rains and floods) affected teaching, research and community service programme of the universities. The result also disclosed that climate change (heavy rain/floods) destroyed universities infrastructural facilities, disrupts energy, water and internet service supply in the universities in North-central Nigeria.